2016
DOI: 10.11648/j.aff.20160503.14
|View full text |Cite
|
Sign up to set email alerts
|

Improving Rice Yield in Tidal Floodplain: Optimizing Seedling Age and Transplanting Date

Abstract: Major constraint of growing rice in south central coastal region of Bangladesh is the tidal submergence of land and crops. Indigenous rice is generally grown in tidal floodplain harvesting poor yield. Transplanting seedlings of optimum age on appropriate date may potentially increase rice yield. We carried out on-farm trials for evaluating growth and yield performance of two indigenous rice varieties (Sadamota and Lalmota) and a high yielding variety (BRRI dhan 44) in response to variable seedling age and tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Seedlings of indigenous varieties grow faster and taller than modern varieties. Our earlier findings [34] indicated that depending on toposequence 45 -60 day-old seedlings of indigenous varieties grow sufficiently taller to cope with depth of tidal flooding immediately after transplanting. Seedlings older than 33 days up to 55 days give better yield under late transplanting for long duration varieties [35].…”
Section: Introductionmentioning
confidence: 83%
“…Seedlings of indigenous varieties grow faster and taller than modern varieties. Our earlier findings [34] indicated that depending on toposequence 45 -60 day-old seedlings of indigenous varieties grow sufficiently taller to cope with depth of tidal flooding immediately after transplanting. Seedlings older than 33 days up to 55 days give better yield under late transplanting for long duration varieties [35].…”
Section: Introductionmentioning
confidence: 83%